Brazilian norms and effects of age and education on the Hayling and Trail Making Tests - Nicolle Zimmermann; Caroline de Oliveira Cardoso; Christian Haag Kristensen; Rochele Paz Fonseca (Trends in Psychiatry and Psychotherapy)
Abstract Objectives To describe normative data for the Hayling Test and the Trail Making Test (TMT) in a sample of Brazilian adults, and to investigate the effects of age and education on test performance. Method A total of 313 (TMT) and 364 (Hayling) individuals with age ranges of 19-39, 40-59, and 60-75 years, and with at least 5 years of formal education, participated in this study. The tests were administered as part of a large battery of a normative project. Individuals were evaluated individually in silent, ventilated rooms at a university clinic. Instrument protocols were scored by trained research assistants and double-checked to ensure data reliability. Results There were major effects of age on the TMT (Time B, Errors B, B-A) and on the Hayling Test (Errors B/15, B/45), and major effects of education on the TMT (Time B, Errors B, B-A) and on the Hayling Test (Time A, Errors B/15, B/45). Interaction effects were found in Time B and B-A for the Hayling Test and in Time A for the TMT. Conclusions Age and education were critical for performance on both verbal and non-verbal executive functions.